2016
DOI: 10.1590/s0100-83582016340100002
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Activity of Parthenium Against Wheat and Canola Differ With Plant Parts and Bioassays Techniques

Abstract: -Phytotoxic effects of invasive weed Parthenium hysterophorus were studied by using whole plant, leaf and root aqueous extracts at 0, 2.5, 5.0, 7.5 and 10% (w/v) concentrations against germination and early seedling growth of wheat and canola. Studies were carried out both in Petri plates with filter paper as substratum placed in controlled conditions and soil-filled plastic pots placed in open environments. Pronounced variation was noted for phytotoxic activity of different plant parts of parthenium, aqueous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The results revealed that C. arietinum was more prone to the higher concentration of parthenium extract. Species-specific difference in sensitivity to aqueous leaf extracts of fresh and dry leaf material of P. hysterophorus was reported in previous studies (Meirse et al, 1987;Khaliq et al, 2016). The results indicated that areas highly infested with parthenium can accumulate a greater amount of allelochemicals and, thus, can pose harmful effects for wheat and other crops (Khaliq et al, 2016).…”
Section: Germination Percentage (%)supporting
confidence: 55%
“…The results revealed that C. arietinum was more prone to the higher concentration of parthenium extract. Species-specific difference in sensitivity to aqueous leaf extracts of fresh and dry leaf material of P. hysterophorus was reported in previous studies (Meirse et al, 1987;Khaliq et al, 2016). The results indicated that areas highly infested with parthenium can accumulate a greater amount of allelochemicals and, thus, can pose harmful effects for wheat and other crops (Khaliq et al, 2016).…”
Section: Germination Percentage (%)supporting
confidence: 55%
“…Various studies have been conducted on the toxic effect of the P. hysterophorus on a wide range of crops. For instance, studies showed that extracts of the weed at lower concentrations (2.5–4%) significantly diminished seed germination, seedling biomass, and chlorophyll content of wheat by 60–75% [ 6 , 7 ] and grain yields of sorghum and maize by 40–97% and 30–60%, respectively [ 5 ]. However, different studies proposed that parthenium biochar can be used as green manure, compost, biocontrol, and soil amelioration that improve the soil physical, chemical, and biological properties and is a source of readily available plant micro- and macronutrients [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…al.Inhibitory Impact ofWhite Cedar… leavesproduce more allelochemicals which may prove lethal to economic crops. Khaliq et al (2016)…”
Section: Resultsmentioning
confidence: 99%